Mussel-inspired 3D networks with stiff-irreversible or soft-reversible characteristics - It's all a matter of solvent. (September 2017) - Vatankhah-Varnoosfaderani, Mohammad; Hashmi, Saud; Stadler, Florian J.; GhavamiNejad, Amin
Abstract: Mostly, catechol groups are used as cross-linkers either based on oxidation to make irreversible networks in presence of oxidizing agent or coordination with metal ions to form reversible networks. However, a systematic study of gelation of catecholic polymer by adding oxidizing agent in non-aqueous solvents are scarce. Here, we report a study of gelation of catecholic polymer by adding oxidizing agent in different media to show the effect of media on behavior of catechol groups. When the gelation performed in an aprotic solvent, the copolymer containing catechol units gelates supramolecularly by H-bonding, yielding reversible and self-healing behavior, while in aqueous solvents irreversibly crosslinked not self-healing gels are obtained. As polymer-bound catechol groups are often studied in water, knowledge of the behavior of catecholic polymer in organic solvents is important to create supramolecular structures with more precisely controlled properties.